Development and Characterization of Electrospun Biopapers of Poly(3-hydroxybutyrate- co-3-hydroxyvalerate) Derived from Cheese Whey with Varying 3-Hydroxyvalerate Contents - Melendez-Rodriguez, Beatriz (2021)
773872 RTI2018-097249-B-C21 BES-2016-077972) (IJCI-2016-29675) 2018022619